The balance between economic development and ecosystem service value in the process of land urbanization: A case study of China's land urbanization from 2000 to 2015. (September 2021) - Cao, Yanni; Kong, Lingqiao; Zhang, Lufeng; Ouyang, Zhiyun
Abstract: Beginning in the 21st century, the world entered a stage of the rapid development of land urbanization. In general, land urbanization sacrifices ecosystem service value for economic value. Optimizing the spatial pattern of land urbanization is the best means of balancing economic development and ecosystem service value. Taking China as an example, through remote sensing and GIS methods, this paper studies the basic situation of regional land urbanization and the distribution of other types of ecosystems from 2000 to 2015, assessing the relationship between the characteristics of regional land urbanization and economic growth and the value cost of ecosystem services. The results show that the spatial differences of land urbanization practices in China is significant and that the extensive development of land urbanization is a serious issue; the urbanization speed of provinces and cities with a larger scale of land urbanization is faster; the intensive, economical and centralized utilization of land urbanization is an effective way to improve GDP per unit area; and the ecosystem service value cost of land urbanization varies significantly among different ecosystem types and regions. For example, the loss of the ecosystem service value of wetland ecosystems due to land urbanization is the greatest, and the cost of the ecosystem service value of Inner Mongolia per 100 million yuan of new GDP is 13.1-fold that of Shanghai. Therefore, to improve the GDP output per unit area and reduce the value cost of ecosystem services, this study draws a series of conclusions and puts forward corresponding policy suggestions that clarify the development mode and priority development area of land urbanization. Highlights: Land agglomeration utilization contributes to the increase in GDP per unit area. The classification of the ecosystems to prioritize protection can reduce the cost of ecosystem service value. The population migration policy should be relaxed. The expansion of land urbanization should give priority to ecosystem service value low-cost areas. Ecosystem service value high-cost areas should change to an intensive urbanization development model.